Perancangan Ui/Ux Website E-Commerce Mercandise Kota Sidoarjo Menggunakan Design Thinking (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
Internet technology has not only transformed societal thought patterns but has also significantly impacted lifestyles, particularly through User Interface (UI) and User Experience (UX). In Indonesia, specifically in the fashion e-commerce sector, there has been rapid growth with over 2 million e-commerce businesses. The UI/UX design process utilizes the Design Thinking method, encompassing stages such as Emphatize, Define, Ideate, Prototype, and Testing. Through the involvement of surveys and interviews, user issues are identified and formulated in the How Might We framework. Figma is employed in the development of UI/UX, resulting in a prototype tested through Usability Testing and the Single Ease Question. The testing outcomes indicate the success of the prototype. Through the application of the Design Thinking method, the design process yields effective solutions, providing an optimal user experience in interacting with the e-commerce merchandise website of Sidoarjo city.